The Impact of Occupational Stress on Job Satisfaction Among Kenyan Primary School Teachers (International Journal of Scientific Research and Management (IJSRM), 2018)
Teaching profession has been hit by high teacher turnover and attrition resulting in shortage of teachers in primary schools. The purpose of this study was to determine the impact of occupational stress on job satisfaction among primary school teachers in Nandi County, Kenya. The main objective was to find the relationship between occupational stress and job satisfaction. This study adopted the explanatory survey research design. The study targeted a total of 1652 primary school teachers. Simple random sampling technique was used to select a sample of 312 teachers. The main data collection instrument was a questionnaire for the teachers. The data collected was analysed through the use of SPSS by regressing and correlating occupational stress and job satisfaction in order to determine the strength of the relationship. The study results indicated that there was a positive relationship between occupational stress and job satisfaction (β = .527, p = .000). The coefficient of determination (R2 = .452) for the estimated model indicated that 45.2% of the deviations in occupational stress contribute towards job satisfaction among primary school teachers. A majority of the primary school teachers are dissatisfied with teaching and if given an opportunity would leave teaching for other professions. The study recommends that it is imperative of government and other stakeholders in education to ensure a high level of career satisfaction for highly qualified and experienced teachers.